Electron heating mode transitions in radio-frequency driven micro atmospheric pressure plasma jets in He/O2: a fluid dynamics approach. (27th April 2021) - Liu, Yue; Korolov, Ihor; Hemke, Torben; Bischoff, Lena; Hübner, Gerrit; Schulze, Julian; Mussenbrock, Thomas
Abstract: A two-dimensional fluid model is used to investigate the electron heating dynamics and the production of neutral species in a capacitively coupled radio-frequency micro atmospheric pressure helium plasma jet—specifically the COST jet—with a small oxygen admixture. Electron heating mode transitions are found to be induced by varying the driving voltage amplitude and the O2 concentration numerically and experimentally. The helium metastable density, and the charged species densities are highly relevant to the electron heating dynamics. By analyzing the creation and destruction mechanisms of the negative ions, we find that the generation of negative ions strongly depends on the O2 concentration. The increase of the electronegativity with the increasing O2 concentration leads to an enhancement of the bulk drift electric field. The distributions of the different neutral species densities along the direction of the gas flow inside the jet, as well as in the effluent differ a lot due to the relevant chemical reaction rates and the effect of the gas flow. The simulated results show that a fluid model can be an effective tool for qualitative investigations of micro atmospheric pressure plasma jets.